A makói kisrégió népességföldrajza - Bajmócy, Péter (Tér és Társadalom, 1996)
The quiet and smooth development of the Makó small-region were interrupted by some traumas in the last 125 years. Fristly after Trianon, secondly after the Parisian peace-congress it become a peripheral area near the state borders. This situation looks a long-lasting process. This traditional agrar-area and it’s development were under the inluence of the industrializing in the fifties, and organizing cooperatives in the early sixties. In the last decades this small-region developed in the shadow of Szeged - one of the some regional centres of Hungary - shows a real dinamic progress. The study shows the development way of a small area, near the state borders, with a weak domain city (Makó) as the centre of the region. It flashed up the endogenous resources which the region can mobilize, to break out of the recent critical part of the population decrease.